Penerapan Metode System Usability Scale Dalam Mengevaluasi User Experience Aplikasi DANA - Nabilla Ajeng Ningtyas; Allsela Meiriza (STMIK Budi Darma, 2023)
In the 4.0 revolution era, digital products were often developed to make it easier, faster, more practical, and cashless for people carry out their daily payment transaction using e-wallet application, one of which is the DANA application. However, reviews on the App Store shows that some DANA application users complained about the problems they experienced when running the application, such as making the transaction process slow and complicated. In order to discover the stage of satisfaction of application users to provide solutions to the DANA application to improve performance of the application, an evaluation of user experience is carry out with the sample used in the research is people who live in Palembang City who have used DANA application. The study output shows that the DANA application obtained an average System Usability Scale score is 62.38 with grade C which stated that the DANA application classified into good category, and had an acceptable level in the